(untitled) (The Pakistan Development Review, 1988)
The political elements in health care policy derive from an observation that the health sector has historically been a "private government". With few exceptions (confined to European countries in the last several decades), the provision of medical services has been a private matter between supplier and consumer, between doctor and patient. Power lover ’’well-being’’ or personal health status was exercised by an active agent with specialized knowledge over a passive recipient without such knowledge or expertise. The concept of self-care obviously lies outside this political framework, although one might argue that the very act of removing oneself from a dyadic relationship is itself a political act. The novel change in recent history has been the willingness, the readiness of governments to enter the domain of hitherto private relationships in order to regulate behaviour of both providers and patients. The political mandate of proactive governments (howsoever they are selected) is exercised through their administrative machinery. Government agencies take the form of bureaucracies comprised of specialized roles based on the division of labour, which in turn are hierarchically arranged and accountable both within the organization and, sometimes, externally to political leaders.